Comprehensive evaluation of rural regional integrated clean energy systems considering multi-subject interest coordination with pythagorean fuzzy information - Yin, Shi; Zhao, Yudan; Hussain, Abrar; Ullah, Kifayat (Engineering applications of artificial intelligence, 2024)
In the development of a comprehensive clean energy system in rural areas, how to evaluate it scientifically and effectively is an urgent problem to be solved. Artificial intelligence has already been widely applied in the field of energy technology, but its application in the comprehensive benefit evaluation is still insufficient. The purpose of this study is to conduct a comprehensive evaluation of the rural, regional integrated clean energy system with coordinated multi-subject interests. Firstly, the interest relationship between the subjects of the participating rural regional comprehensive clean energy system is analyzed. And, the comprehensive benefit evaluation index system is established based on farmers, rural grid, new energy investment operators, government and interest subject reciprocity partners. Secondly, Sugeno-Weber aggregation operators are more flexible and used to acquire smooth aggregated outcomes from a group of information in a single set. Moreover, an algorithm of the multi-attribute decision-making process also reveals the supremacy and reliability of the research work. A case study is established to evaluate the rural integrated clean energy system with coordinated multi-subject interests. The results are as follows. The index system reflects the characteristics of the comprehensive clean energy system in rural areas, such as environmental characteristics, economic characteristics, safety characteristics and clean energy characteristics. The advantages and validity of developed research work are proved by comparing the findings of pioneered approaches with existing mathematical operators. The ranking of suitable energy sources is Solar power > Biomass energy > Geothermal energy > Wind and hydropower based integrated clean energy system.